Characterizing wheat genotypes for zinc efficiency based on high grain yield and zinc uptake - Abbas, Muhammad; Depar, Nizamuddin; Akram, Muhammad Ahmed; Irfan, Muhammad; Sial, Niaz Ali; Afzal, Javaria; Shah, Javaid Ahmed; Ullah, Sana (Journal of Pure and Applied Agriculture, 2025)
Given the substantial loss of crop productivity in zinc (Zn) deficient soils, the development of cultivars with improved absorption and utilization capabilities is required to sustain the productivity of low input agricultural systems. In this regard, field experiments were conducted over two years to test ten wheat genotypes for Zn efficiency at two Zn levels (0 and 5 kg Zn ha-1). The data analysis revealed that the effects of years and years’ interactions with genotypes and Zn levels were non-significant. However, genotypes and Zn levels significantly (P < 0.05) affected grain yield, Zn uptake and Zn efficiency indicators. Zn stress factor (ZnSF) varied between 3.80 to 13.39%, signifying the differential sensitivity of wheat genotypes to Zn deficiency. For low, medium, and high-performance rankings at each Zn level, each parameter was given an index score of 1, 2, and 3, respectively. Additionally, the genotypes were divided into five groups according to their total zinc uptake and grain yield at low zinc. With a total index score of 26, SDT-V11 was classified as HGY-HZn (High grain yield-high Zn uptake) genotype. With corresponding total index scores of 25, 23, and 22, the three genotypes—SDT-V8, AST-V2, and NIA-AS-14-1—were assigned to the HGY-MZn (High grain yield-medium Zn uptake) group. Zincol-2016, with the least cumulative index score of 18, was categorized as medium grain yield-low Zn uptake (MGY-LZn) cultivar. This kind of classification will help future breeding efforts to increase the efficiency of nutrient utilization.